بێکارى و دەرئەنجامە ئابوورییەکانى لەگەڵ ئاماژەیەکى تایبەت بە هەرێمى کوردستانى عێراق - سعید, محمد رووف (Sulaimani Journal for Humanities, 2002)
Iraqi Kurdstan like the developing countries is suffering from population problms which we can indicat throughout increased population size under the age of working as a result of the high rate of population growth wich cause the decrease of the size of population of the age working and the size of lahour force that must play a great role in the development process but unfehrtunately these countries Suffer also from all sorts of unemployment that case a great loss of human abilities and wandaring nunmerous development opportunities therefore the necessity increases to confidence effectual ways dependence to solve unemployment problem or at least to decreas its rate by constructing importance projects leading development process and deminishing the defferences with separate the defferent reagion to push the development process and to obtain many opportunities of work to execute unemployment .